Utilizing computer simulation in large scale cyber-physical systems - Ranta, Timo (My University, 2019)
As computational power gets cheaper and more available and tools used for building computer simulations get better companies are starting realize the benefits, cost savings and efficiency improvements they can achieve utilizing computer simulation. Using some form of computer simulation to solve a problem, identify optimal solution or train an employee for example has been getting more and more common in the recent years. Simulators are getting recognized as a quite optimal training method and some authorities are even starting to require a certain number of simulator training hours before issuing a permit to start practicing with a real-world counterpart. This thesis covers the history, tools used, application areas, benefits and challenges of computer simulation and simulation model building with the goal of being able to identify best practices and possible pitfalls and how to avoid falling into them. Once the history and theory behind the subject has been discussed a case study is presented and the next chapters will go over a real-world simulator building process that took place in Naatali power plant mainly during the year 2018. An operator training simulator was built of the new power plant unit and it is now used to train the power plant operators to optimally handle different operating scenarios. The foundation of the tools used was a modeling language called Modelica. The reasons for choosing this approach will be covered as well as the benefits and drawbacks of the decision and whether or not there would have been better options available. The issues identified during the project are also discussed and how they were or could have been avoided or dealt with. This case study approach is optimal for reflecting the theory on a real-world use case and to see how the different methods described in studies are actually used in a real modeling project. After reflecting the actual execution to the theory behind it reasons will be given to why Modelica was a good choice for the modeling language used at this particular project, what could have been done better and what issues still remain for the following projects to solve. Both Naantali power plant and their operators benefit from a custom-built training simulator and investing in a state-of-the-art simulator was a good investment. The tools and methods that the simulator provider used were also justified and, in most cases, optimal.
Keywords: simulation, Modelica